Postoperative angioedema induced by angiotensin-converting enzyme inhibitor: case report - Flora Margarida Barra Bisinotto; Beatrice Cavalcanti Seabra; Fernando B. Prata Lóes; Laura Bisinotto Martins; Luciano Alves Matias da Silveira (Brazilian Journal of Anesthesiology, 2019)
Background and objectives: Angioedema is a potentially fatal condition that may occur at any time in the perioperative period. It may result from histamine release, hypersensitivity reaction to drugs, or be triggered by bradykinin, in non-allergic reactions of hereditary or acquired etiology. The aim of this report is to report a case of angioedema in the early postoperative period in a patient on antihypertensive medication involving angiotensin-converting enzyme inhibitors. Case report: A 67-year-old male, Afro-descendant, hypertensive, and taken enalapril maleate underwent orthopedic shoulder surgery under general anesthesia combined with brachial plexus block. The procedure lasted 3 hours uneventfully. After discharge from the post-anesthesia care unit, the patient presented with angioedema and severe airway impairment. Tracheal intubation was attempted but it was impossible due to edema affecting the lips, tongue, and oropharyngeal region Emergency cricothyroidotomy was performed. The onset of angioedema had no causal relationship with the administration of any medication; there were no cutaneous manifestations and also not response to therapy for hypersensitivity reaction to drugs, such as antihistamines, corticoid, and adrenaline. It was considered to be mediated by bradykinin, as the patient had already had two similar episodes and was on regular medication (enalapril). The evolution was satisfactory. Conclusion: Angioedema is a potentially fatal condition when it affects the airway, and should be recognized by anesthesiologists and physicians working in the emergency departments. Resumo: Justificativa e objetivos: O angioedema é uma condição potencialmente fatal que pode surgir em qualquer momento no perioperatório. Pode decorrer da liberação de histamina, em uma reação de hipersensibilidade a drogas ou ser desencadeado pela bradicinina, em reações não alérgicas, de etiologia hereditária ou adquirida. O objetivo desse relato é descrever um caso de angioedema, no pós-operatório imediato, em um paciente em uso de medicação anti-hipertensiva da classe dos inibidores da enzima conversora da angiotensina. Relato de caso: Paciente de 67 anos, masculino, negro, hipertenso e em uso do maleato de enalapril, foi submetido a cirurgia ortopédica de ombro sob anestesia geral associada a bloqueio do plexo braquial. O procedimento durou 3 horas, sem intercorrências. Após a alta da sala de recuperação pós-anestésica, apresentou angioedema com grave comprometimento das vias aéreas. Tentou-se fazer intubação traqueal, mas foi impossivel devido ao edema que acometia os lábios, a língua e região orofaringeana. Fez-se a cricotireoidostomia de emergência. O aparecimento do angioedema não apresentou relação causal com a administração de qualquer medicação, não houve manifestações cutâneas e também não respondeu à terapêutica para reação de hipersensibilidade a drogas, como anti-histamínicos, corticoide e adrenalina. Foi considerado como mediado pela bradicinina, pois o paciente já havia apresentado dois episódios semelhantes e estava em uso regular de medicação (enalapril). A evolução foi satisfatória. Conclusão: O angioedema é uma condição potencialmente fatal quando atinge as vias aéreas e deve ser de conhecimento do anestesiologista e dos médicos que trabalham nos setores de emergência. Keywords: Angioedema, Bradykinin, Enalapril maleate, Angiotensin-converting enzyme, Angiotensin-converting enzyme inhibitors, Palavras-chave: Angioedema, Bradicinina, Maleato de enalapril, Enzima conversora da angiotensina, Inibidoras da enzima conversora da angiotensina